KECERNAAN RANSUM SAPI BALI DENGAN KONSENTRAT FERMENTASI BERBASIS LUMPUR SAWIT DAN BAHAN PAKAN LOKAL - Irma Badarina; Jarmuji Jarmuji; Dodi Permadi Gultom (AGROINTEK, 2017)
The aim of this research was to evaluate the dry matter and organic matterdigestibility in vivo of Bali cattle diet that supplemented with fermented concentrate ration based from palm oil sludge and several local feed sources. Fifteen Bali cattles with 2 years old and the range of live weight 184,5±3,63 kg were distributed into three treatments and five replication in Completely Randomized design. The treatment was the level of concentrate supplementation, They were P1 (10kg/day), P2(7,5kg/day) and P3(5kg/day). The forage and the rice straw were adjusted as much as 10 kg/day and 1 kg/day, respectively. The composition of fermented concentrate consisted of palm oil sludge (70%), rice bran (10%), coffee husk (10% ) and coconut press fiber (10%). As bioactivator used”Bionak”as much as 0,3%. The an aerob fermentation took time a week. The result showed that up to the highest level (10kg/day) the supplementation of fermented concentrate ration enhanced the consumption and the digestibility of the whole rations.